4-(3x+2)=7x-2(4x-3)

Simple and best practice solution for 4-(3x+2)=7x-2(4x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4-(3x+2)=7x-2(4x-3) equation:


Simplifying
4 + -1(3x + 2) = 7x + -2(4x + -3)

Reorder the terms:
4 + -1(2 + 3x) = 7x + -2(4x + -3)
4 + (2 * -1 + 3x * -1) = 7x + -2(4x + -3)
4 + (-2 + -3x) = 7x + -2(4x + -3)

Combine like terms: 4 + -2 = 2
2 + -3x = 7x + -2(4x + -3)

Reorder the terms:
2 + -3x = 7x + -2(-3 + 4x)
2 + -3x = 7x + (-3 * -2 + 4x * -2)
2 + -3x = 7x + (6 + -8x)

Reorder the terms:
2 + -3x = 6 + 7x + -8x

Combine like terms: 7x + -8x = -1x
2 + -3x = 6 + -1x

Solving
2 + -3x = 6 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
2 + -3x + x = 6 + -1x + x

Combine like terms: -3x + x = -2x
2 + -2x = 6 + -1x + x

Combine like terms: -1x + x = 0
2 + -2x = 6 + 0
2 + -2x = 6

Add '-2' to each side of the equation.
2 + -2 + -2x = 6 + -2

Combine like terms: 2 + -2 = 0
0 + -2x = 6 + -2
-2x = 6 + -2

Combine like terms: 6 + -2 = 4
-2x = 4

Divide each side by '-2'.
x = -2

Simplifying
x = -2

See similar equations:

| 3+5(4+2)= | | 6-3+5=3+5 | | 3x-22=2+3 | | -22+8x-4x=30 | | 5x+3-2x=7-4x+1 | | 4/x^6y^6*4x/y^4 | | 2.5x-13=2 | | 2e(x+2)=5 | | u^2+3u+uv+3v=0 | | X-12+x=38 | | X-13=6+2x | | 3x+7=9x-2 | | 4x-21=7 | | -5-21= | | 20x+6=4x-9 | | -5(3y-9)-y=-4(y-4) | | 5(5X+2)-6=25X+4 | | 6[3y-2(y-1)]-2+7=0 | | 2x+29-8x=5 | | x/6-7=-5 | | 4x-8y-9x-7y= | | -6.362-0.9n=0.9(2.3-0.8n)+2.3n | | 4X-6=4(X-1) | | -2x(x-1)+5x=2(2x-1) | | Y3/4x+7 | | log(x+1)=5.8 | | -9(k+9)-8= | | 24+-5y+5*24+-5y+11=35 | | 12+1/3y=-1 | | 13x-5=4x+9 | | 12x+4+2x=39 | | 8m+3m=12m+9 |

Equations solver categories